Informasi Evaluasi Tata Kelola Teknologi Informasi Pada Klinik Menggunakan Framework Cobit 5 - Meisyah Nadila Mukti; Raissa Amanda Putri; Aninda Muliani Harahap (Universitas Budi Darma, 2026)
The rapid advancement of information technology has driven healthcare facilities to optimize the use of information systems to support operations and data management. The UINSU Medan Primary Outpatient Clinic has been using the eClinic system; however, a standardized evaluation of information technology governance has not been systematically established. This study aims to design and implement a web-based information system for evaluating IT governance using the COBIT 5 framework. The method employed is quantitative descriptive with an evaluative approach through the Process Assessment Model (PAM) in the Evaluate, Direct, and Monitor (EDM) domain, covering processes EDM01, EDM02, and EDM05. Data were collected via a web-based questionnaire from five respondents consisting of administrators, doctors, and nurses. Black-box testing confirmed that all system features function as intended. Evaluation results indicate that EDM02 and EDM05 achieved the target Capability Level 3, while EDM01 only reached Level 2, with a gap of +1 level due to the unmet Process Definition attribute (PA 3.1). Improvement recommendations focus on standardizing and documenting IT governance operational procedures at the clinic.